Comparative assessment of biologics in treatment of psoriasis: drug design and clinical effectiveness of ustekinumab - Ignacio Garcia-Valladares; Raquel Cuchacovich; Luis R Espinoza (Dove Medical Press, 2011)
Ignacio Garcia-Valladares, Raquel Cuchacovich, Luis R EspinozaSection of Rheumatology, Department of Internal Medicine, LSU Health Sciences Center, New Orleans, LA, USAAbstract: The development of psoriasis and psoriatic arthritis is a multistep process that leads to chronic or recurrent inflammation. Recent studies have suggested the importance of T helper (TH)1 and TH17 cells, accessory cells, and proinflammatory cytokines in the pathogenesis of the enthesis, synovium, and skin involvement in psoriasis in the presence of susceptibility genes that remain quiescent until triggered. Biologics, such as soluble CTLA-4 immunoglobulin, tumor necrosis factor (TNF) inhibitors, and ustekinumab, inhibit T cell activation which eventually leads to further stimulation of the interleukin 12, 17, and 23 axis, TNF-α, and lymphotoxin-α. Treatment with TNF-α blockers has been effective in refractory psoriasis and psoriatic arthritis, but there is still a subgroup of patients who do not respond to TNF inhibitors and, paradoxically, when treated, may develop TNF-induced psoriasis. Ustekinumab, because of its different mechanism of action at the level of the interleukin 12, 17, and 23 pathways, is an alternative treatment for this group of patients.Keywords: psoriasis, psoriatic arthritis, biologics, ustekinumab, tumor necrosis factor inhibitors